CYBER-SECURITY CHALLENGES IN DIGITAL LIBRARIES - Inam Magsi; Nusrat Shaheen; Waqas Ahmed Channar; Mubarak Ali; Zubair Lakho; Adeel Ahmed (Review Journal of Social Psychology & Social Works, 2025)
Digital repositories have transformed information accessibility, yet they encounter substantial cyber-security hurdles. These include data infiltrations, unauthorized system entry, and malware incursions, which jeopardize the integrity and confidentiality of digital assets. This study delves into the ramifications of cyber-security violations in digital repositories, prevalent digital threats, optimal security practices, and emerging security trends. A combination of quantitative surveys and qualitative interviews is employed to assess existing protective measures. The findings underscore the necessity for robust identity verification, data encryption, and proactive security strategies to fortify digital collections. As digital libraries continue to evolve, ensuring their resilience against cyber threats remains a priority for information security professionals and institutions worldwide.